It's all or nothing, Vale - Arango, Andrea Beatriz (Random House Children's Books, 2025)
"No one knows hard work and dedication like Valentina Camacho. And Vale's thing is fencing. She's the top athlete at her fencing gym. Or she was--until the accident. After months away, Vale is finally cleared to fence again, but it's much harder than before. Her body doesn't move the way it used to, and worst of all is the new numberone: Myrka. When she sweeps Vale aside with her perfect form and easy smile, Vale just can't accept that. But the harder Vale fights tocatch up, the more she realizes her injury isn't the only thing holding her back. If she can't leave her accident in the past, then what does she have to look forward to?"--